(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The demand for safe, minimally processed, and healthy foods from consumers has created the need to develop new technologies to meet these requirements. These technologies must be environmentally sustainable. Therefore, the objective of this study was to evaluate the effect of pretreatment with Static Magnetic Field (SMF) on the fermentation of pork meat emulsions. An emulsion was prepared with the following composition: 15.03% protein, 24.64% fat, 57.64% water, 1.90% salt, 0.02% nitrite, 0.1% culture, and 0.67% lactose. The emulsion was subjected to SMF treatment at 4.5mT for 0, 3, 5, and 10 minutes. Subsequently, the samples were stored for 20 days at room temperature. The pH, color, stability, and moisture were evaluated on days 1, 4, 8, 12, 16, and 20, and the microbiota was analyzed on days 1 and 20. It was found that the emulsion is stable and its moisture content does not vary. The pH does not vary with the pretreatment but decreases over the storage period. The microbial activity of Lactobacillus bulgaricus is affected by the pretreatment but shows recovery after 4 days of storage. The lightness decreases with the pretreatment, and this effect persists until day 4. In the color parameter a*, the pretreatment causes an increase in the scale, with this change being proportional to the treatment time. The b* parameter shows a decrease until day 8 and then exhibits the opposite behavior. These changes are related to the treatment time. There are reductions in total coliforms to 200 CFU/g and fecal coliforms to <3 CFU/g in the samples due to storage conditions.